Trends in Antimicrobial Drug Resistance of Streptococcus pneumoniae Isolates at Jordan University Hospital (2000-2018) - Malik Sallam; Jumana Abbadi; Anas Natsheh; Nidaa A. Ababneh; Azmi Mahafzah; Gülşen Özkaya Şahin (MDPI AG, 2019)
Antimicrobial drug resistance (AMR) in pneumococci complicates the treatment of serious pneumococcal infections. Country-specific AMR patterns can help to establish guidelines for empiric therapy. The aim of the current study was to analyze the distribution of AMR among Streptococcus pneumoniae isolates at Jordan University Hospital (JUH) during 2000–2018. Paper-based and electronic clinical data registry records from 2000 to 2018 were retrospectively analyzed to study the AMR among pneumococcal isolates at JUH. Temporal trend analysis was done using two-tailed linear-by-linear test for association. The total number of unique pneumococcal isolates that were identified was 556, of which 544 isolates had antimicrobial susceptibility testing results. The most frequent specimens were eye (n = 117, 21.0%), bloodstream (n = 93, 16.7%) and sputum (n = 81, 14.6%). Invasive infections represented 23.6% of all unique isolates. The overall susceptibility of S. pneumoniae isolates during the study period to different antimicrobials was: 100% to vancomycin, 97.7% to ceftriaxone, 97.1% to cefotaxime, 94.9% to chloramphenicol, 89.7% to penicillin, 83.8% to levofloxacin, 67.7% to clindamycin and 52.1% to erythromycin. The prevalence of multi-drug resistance (MDR) was 8.6% (95% confidence interval: 6.4–11.5%). Trend analysis showed an increase in the prevalence of non-susceptibility to erythromycin, clindamycin and levofloxacin (p < 0.001). MDR prevalence increased from 1.6% in the first quarter to 14.6% in the fourth quarter (p < 0.001). The incidence of invasive infections declined over the study period (p < 0.001). The increase in the prevalence of AMR and MDR among pneumococcal isolates in Jordan demands judicious use of antimicrobials and regular surveillance of resistance.